Nekateri teoretični in praktični vidiki zavarovane dobrine pri menedžerskem deliktu po 240. členu KZ-1 - Kozina, Jože (Podjetje in delo, 2016)
Undoubtedly it is to be agreed that plurality of opinions and views in the post-modern society represents an important civilizational value. There are, however, areas where its presence is less welcome. One of them also embodies the area of criminal law that applies to legal goods that are to be protected by the incriminating clauses of Criminal Code (Kazenski zakonik - KZ-1) and regarding which it would have to be crystal clear to the legislator what good is to be protected before each incrimination of certain behaviour. If this imperative is not met, and this is especially evident in cases of managerial offences, we face a situation as it is now and the fact that encroachment of its legal essence is done "across and crosswise every so often" is only one of the disastrous aspects of the disorientation in criminal law.
Keywords: kazniva dejanja; managerji